PENGARUH KETERLIBATAN KERJA, MOTIVASI INTRINSIK DAN BUDAYA ORGANISASI TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) DI DINAS LINGKUNGAN HIDUP PROVINSI SUMATERA UTARA - Hasrito Siregar; Ahmadi .; Zainuri .; Yuni Susanti; Rudi Aritonang (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
The research is tittled “The Effect of Communication Competency, Emotional Intelegency and This study discusses work motivation, intrinsic motivation, and organizational culture on the performance of the State Civil Apparatus (ASN) in the Environmental Service of North Sumatra Province. This research was conducted at the Environmental Service of North Sumatra Province which is located at Jl. Tengku Daud No. 5, Medan City, North Sumatra. This research uses quantitative methods with the type of research using secondary and primary data. The population of this study is all employees of the North Sumatra Province Environmental Agency, men and women who support 112 people. Samples were taken as many as 54 people. Data were analyzed using multiple linear regression, coefficient of determination (R2), partial test (t-test) and simultaneous test (F-test) using SPSS version 19.0. The results of the analysis show that of the three independent variables included in the regression model for involvement, intrinsic motivation and organizational culture. The variable work involvement of the State Civil Apparatus (ASN) in the North Sumatra Province Environmental Service has a positive and significant influence on the performance of the State Civil Apparatus (ASN). Based on the results of partial significance testing (t-test), the tcount value of 2.705 1.674 was obtained with a significance level of 0.00 0.05. Intrinsic motivation of the State Civil Apparatus (ASN) in the North Sumatra Province Environmental Service has a positive and significant impact on the performance of the State Civil Apparatus (ASN). Based on the results of partial significance testing (t-test), the tcount value of 3.742 1.674 was obtained with a significance level of 0.00 0.05. Organizational culture in the North Sumatra Province Environmental Agency has a negative influence on the performance of the State Civil Apparatus (ASN). The results of the partial significance test (t-test) found t-value of -1.19557 t-table -1.674 with a significance level of 0.056 0.05. The results showed that the variables of work involvement, intrinsic motivation, and organizational culture together had a significant positive effect on performance. This is evidenced by the results of the regression test statistics obtained values with a probability of 0.000 0.05, it can be explained that work involvement, intrinsic motivation, and organizational culture have a significant positive effect on performance. Then the fourth hypothesis is accepted.